A Review of Housing and Food Intersections: Implications for Nurses and Nursing Research. Issue 4 (December 2019) - Vold, Lindsey; Lynch, Meghan; Martin, Wanda
Study Background: Quality, accessibility, and affordability of housing and food are public health and nursing concerns. Yet, intersections between housing and food security are relatively understudied. Purpose: The purpose of this article is to examine the evidence describing the relationship between food security and housing interventions, and second, describing specific opportunities for targeted strategies for nursing practice and research. Methods: Arksey and O'Malley's scoping review method was followed to search housing and food security research. A database search identified 46 studies that were mapped onto a social ecological theory to understand the micro, meso, exo, and macro interventions. Results: Three major recommendations were identified. Micro-system recommendations include primary care screening for low-income groups. Meso- and exo-system recommendations focus on creating partnerships in research and enhancing social housing. Lastly, macro-system recommendations focus on challenging housing affordability standards. The major gap in the literature is addressing healthy housing. Conclusion: Broadening housing interventions to include comprehensive approaches to meeting individuals' needs offers more than simply packaging two interventions together. There is a significant moment in nursing in which nurses are witness to a paradigmatic shift in the ways to approach housing and food security.